Grupo escolar em Minas Gerais: análise da legislação na Primeira República (1906 1924) - Oliveira, Sandra Maria de (2012)
This study is anchored in the History of Education research, specifically in Educational Legislation field of Decrees, Laws and Regulations. Educational Legislation (1906- 1924) was analyzed, in search of changes and transformations related to Minas Gerais school groups. Methodological procedure comprised Bibliographical Research and Documentation studies regarding Decrees, Laws and Regulations of Federal and State of Minas Gerais Legislations, as well as some messages from State of Minas Gerais presidents. School groups have emerged in 1892, in São Paulo, within the Republican Political Project of Social Reform and Diffusion of Popular Culture. In Minas Gerais, for school group implementation, there were intense debates in Legislative Assembly (1893-1906) on the scarcity and poverty of mining schools, lack of teacher preparation, resulting in illiteracy. Brazilian Republic political was influenced by this State, and can develop a thriving economy, ensuring Minas Gerais residents a schooled knowledge. Thus, in 1906, during João Pinheiro s government, Law nº 439 was implemented and the object of this was the Minas Gerais State Reform of Primary, Normal, and Higher Education. For this, appropriate and effective measures were adopted for compulsory primary education. This Law was regulated by Decree n. 1960 (1906), which proposed guidelines for school group functioning and class categories of workers (director, inspector and teacher) with their respective roles inside the mining public school. In this sense, the miner regulation, pointed out inspector duties as a government representative, an authority that oversaw and inspected teaching in order to enforce the standards set by the State. For the director, a prestige position in local society belong the role of mediator between school and state government, responding to problems and internal constraints of school group. Teachers were responsible to adapt student for changes, representing a social relationship between family and school, and to transmit knowledge, moral and cultural values. Students in the civilizing process of republican society should get: good manners, hygiene and health, and moral values to become a responsible citizen by the new order, according to the requirements and society. Through legislation analysis, we can conclude that there were several changes in duties of school professionals, in the period selected for this research, as well as changes in education hierarchy and bureaucratization. Therefore, the Educational Legislation served to efforts of a Republic who saw education as a process and a product in the development of a socialized individual, responsible for the new order, respecting the rules and working for the country\'s growth.